(3MGTjI eYGde GdOjfs - (3GdHgHgGfj, GdCSJGP GdCcHQ, GdhMjO, eMeO HGbQ Hf eMeO Cced, (B1206 (3g`s ((3YHO Gddg Hf eMeO MSfs)
(3ChdgG (B:s
(3HSe Gddg (B.. (3hHGdCaYGd Ef bdJ ef LedI GdCaYGd aYd GdeUfa hgh MLI cbhdg hGdYde Hg aj GdCMcGe GdTQYjI GdaQYjI abg acja jNQL Yf JYQja Gdabg , bdJ aYdg cbhdg ef LedI GdCOdI(B...s
(3BNQgG (B:s
.. (3hHGdLedI EPG bGd Cf GdTjA cPG adGHO ef GdMce HYOe chfg cPG TQYG cd ef GdKHhJ ef GdTQY HdG THgI fYe aj GdeDbJ hEdG aj GdPj eKd GdeDbJ djS cPc hhLgg hGVM (B, (3JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\ 49s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3CUhd Gdabgs